Preliminary evaluation of black sigatoka resistance in IITA plantain hybrids - Gauhl, F.; Mobambo, K.; Pasberg-Gauhl, C.; Swennen, Rony L.; Vuylsteke, D.R. (1994)
A clonal evaluation trial of llTA plantain hybrids for black Sigatoka (85, resistance was established in October 1990. The trial included the three tetraploid hybrids TMPx 5484. TMP" 548-9and TMP" 5974. and their non-treated and fungicide-treated female plantain parent Obino l'Ewa' (French plantain}. Differences between the BS-susceptible plantain parent and the hybrids were distinct. In the first week 01 April 1991 {6 months after printing' the number of standing leaves in the non-treated plantain was 10.0, in tile fungicide-treated plantain 12.9. whereas TMP" 548•4 and TMPK 548-9 hold 11.4 and TMP" 597-4 had 11. 9leaues. The youngest leaf spotted (spot was dry center} in the non-treated plantain was 5.5, in the fungicide-treated plantain 6.6, in TMPx 548-4 and TMP" 548•9 11.2 and in TMP" 59749.9. The overage percentage per plant of leaf area with symptoms was 21.5. 18.3, 2.2, 2.1 and 2.9, respectively. For the parameter "youngest leaf with symptoms", the value ranged between 2.0 and 2.5.